Adaptive fault tolerant control for cantilever thick plates with piezoelectric patches - Azin Nadi; Mojtaba Mahzoon; Ehsan Azadi Yazdi (Scientific Reports)
Abstract This paper presents a novel adaptive fault-tolerant control (AFTC) framework for systems with piezoelectric sensor patches, specifically targeting sensor faults and external disturbances. The proposed method ensures robust control of cantilever thick plates by integrating adaptive estimation to simultaneously handle sensor faults and system uncertainties, maintaining stability despite issues like drift, bias, loss of accuracy, and effectiveness. Unlike traditional approaches that address sensor faults individually, our method provides a comprehensive solution backed by Lyapunov-based stability analysis, demonstrating uniform ultimate boundedness under various fault conditions. Extensive simulations validate the controller’s superior fault compensation and disturbance rejection compared to Backstepping Sliding Mode Control (BSMC). Under fault-free conditions, the baseline controller achieves accurate tracking, while the AFTC shows significant improvement in trajectory tracking and adaptation when faults are introduced, with minimal performance degradation. This work extends fault-tolerant control strategies to complex systems, including those involving piezoelectric elements, providing a foundation for future research in this area, which has been largely unexplored.